2011
DOI: 10.1155/2011/534069
|View full text |Cite
|
Sign up to set email alerts
|

The Antiinfective Effects of Velvet Antler of Formosan Sambar Deer (Cervus unicolor swinhoei) on Staphylococcus aureus‐Infected Mice

Abstract: We assayed the effects of velvet antler (VA) of Formosan sambar deer (Cervus unicolor swinhoei) and its extracts on the anti-infective activity against pathogenic Staphylococcus aureus in vitro and in vivo in this study. In vitro data indicated that the VA extracts stimulated the proliferation of resting splenocytes and macrophages in a dose-dependent manner up to the highest concentration used (150 μg mL−1). The production of proinflammatory cytokines (TNF-α, IL-6, IL-12) by lipoteichoic acid was significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 44 publications
0
25
0
Order By: Relevance
“…Furthermore, extracts of deer bones affected macrophagic activation in S . aureus -infected mice [22]. In this study, we demonstrate that water extract of deer bones (hereafter, NG) alleviates neutropenia through activating macrophages.…”
Section: Introductionmentioning
confidence: 80%
“…Furthermore, extracts of deer bones affected macrophagic activation in S . aureus -infected mice [22]. In this study, we demonstrate that water extract of deer bones (hereafter, NG) alleviates neutropenia through activating macrophages.…”
Section: Introductionmentioning
confidence: 80%
“…In a phase II trial, DAE showed great improvement for rheumatoid arthritis compared to placebo (Allen et al, 2002). The production of proinflammatory cytokines, such as TNF-␣ and IL-6, by lipoteichoic acid was significantly reduced after treatment with DAE in Raw 264.7 cells and peritoneal macrophage cells (Dai et al, 2011). In addition, the effect of DAE on bone health has been studied.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these, VA extract can also boost the immune system in a general way [8]. VA extract has markedly anti-infective effects on staphylococcus aureus-infected mice [9], and demonstrates significant enhancement of immune function of lymph, spleen, and bone marrow [10], as well as enhancement of phagocytes and immunoglobulin levels in mice [11]. Although these activities of VA extract had been observed in a series of animal experiments, it is uncertain about which single component of interest in VA had played a leading role in these effects.…”
Section: Introductionmentioning
confidence: 99%